2006
DOI: 10.1063/1.2357845
|View full text |Cite
|
Sign up to set email alerts
|

Transmission electron microscopy investigation of the structural damage formed in GaN by medium range energy rare earth ion implantation

Abstract: Articles you may be interested inA mechanism for damage formation in GaN during rare earth ion implantation at medium range energy and room temperature

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
45
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 33 publications
9
45
1
Order By: Relevance
“…For GaN, the formation of a nanocrystalline layer from the surface occurs above 2x10 15 Eu/cm 2 , when the stacking fault network has reached the surface [10,11]. For AlN, the stacking fault network does not reach the surface and an amorphization in the bulk, around Rp, has been reported for fluences higher than 10 17 Eu/cm 2 [12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For GaN, the formation of a nanocrystalline layer from the surface occurs above 2x10 15 Eu/cm 2 , when the stacking fault network has reached the surface [10,11]. For AlN, the stacking fault network does not reach the surface and an amorphization in the bulk, around Rp, has been reported for fluences higher than 10 17 Eu/cm 2 [12].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the literature about ion implantation and correlated irradiation effects on GaN is becoming more and more complete [5][6][7]. In particular, the mechanisms of damage formation have been shown to differ from the conventional scheme of amorphization [8][9][10][11]. In the case of AlN, only a few reports are available on electronic quality layers, as was shown, this material is resistant to ion implantation damage formation and the amorphization has been shown to take place at very high implantation fluences (~10 17 at./cm 2 ) [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig. 3c, exciting the g=1-100 reflection, shows that, in addition to the defect clusters, a complex network of basal stacking faults (BSFs), both intrinsic (I1 and I2 type) and extrinsic (E), and prismatic stacking faults (PSFs) 21,22 has been generated during the implantation. A high resolution example of one I2 BSF inside the implanted region is exhibited in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, TEM investigations for GaN Gloux et al, 2006) and ZnO (Perillat-Merceroz et al, 2011) showed the prominence of these defect types in both materials for room temperature implantations.…”
Section: Implantation In Gan and Znomentioning
confidence: 99%